Acute Liver Failure/Injury Related to Drug Reaction With Eosinophilia and Systemic Symptoms: Outcomes and Prognostic Factors. Issue 8 (August 2017) - Ichai, Philippe; Laurent-Bellue, Astrid; Saliba, Faouzi; Moreau, David; Besch, Camille; Francoz, Claire; Valeyrie-Allanore, Laurence; Bretagne, Sylvie Roussin; Boudon, Marc; Antonini, Teresa Maria; Artru, Florent; Pittau, Gabriella; et al.
Abstract : Background: Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare severe adverse drug-induced reaction with multiorgan involvement. The outcome and prediction of those patients who develop severe acute liver injury (sALI) or acute liver failure (ALF) remain little known. Methods: A multicenter retrospective study of patients admitted with a diagnosis of DRESS-related sALI or ALF. Histological review was performed on liver core biopsies from native livers. Results: Sixteen patients (11 women, 5 men; mean age, 39±17.2 years) were classified as having definite (n=13) or probable (n=3) DRESS. At admission, 3 patients had hepatic encephalopathy; median levels of prothrombin time, INR, and total bilirubin were, respectively, 33% (Q1-Q3, 21-41), 2.74 (1.98-4.50), and 94 μmol/L (Q1-Q3, 39.5-243.5). Nine patients received corticosteroid therapy. Overall, 9 patients improved spontaneously and 7 worsened (liver transplantation [LT] (n=5), deceased (n=2)). Transplantation-free and post-LT survival was 56% and 60%, respectively. After LT, DRESS recurrence was observed in 3 of 5 patients. Systemic corticosteroid therapy was not significantly associated with a clinical improvement. In the multivariate analysis, factor V level less than 40% at day 0 and factor V levels of 40% or greater at admission but decreasing at day 2 were associated with worse outcome. Pathological findings (n=7) revealed atypical lymphoid infiltrates, Kupffer cell hyperplasia with erythrophagocytosis, and an inconstant presence of eosinophils. Conclusions: The spontaneous prognosis of patients with sALI/ALF due to DRESS is poor and was not improved by corticosteroid therapy. Histology is helpful to establish diagnosis. Dynamic variables regarding factor V values are predictive of a poor outcome. Abstract : In this multicenter retrospective study, the authors report on 16 patients with drug reaction with eosinophilia and systemic symptoms complicated with severe acute liver injury or acute liver failure highlighting its poor spontaneous prognosis, lack of efficacy of steroids, importance of histology to establish diagnosis and good predictive value of factor V dynamic changes. Supplemental digital content is available in the text.